Transparency, Policy Outcomes, and Incumbent Support. (13th March 2019) - Aguiar‐Conraria, Luís; Magalhães, Pedro C.; Veiga, Francisco J.
Summary: Government transparency has been discussed both as a way to decrease informational asymmetries between officeholders and citizens and as part of what makes for procedurally fair governance. These two different lines of argument generate predictions about how transparency should change voters' reactions to economic and policy outcomes. First, under high transparency, voters should respond less positively to fiscal expansions. Second, they should become more sensitive to incumbents' ability to deliver outcomes that generate benefits in the long‐run than to current tangible benefits. We test these arguments using municipality level data in Portugal. Controlling for variables that previous research has shown to drive electoral support for incumbents in local elections, only in the least transparent municipalities is support positively related with increases in local current expenditures, budget deficits, and municipal wages. Instead, where transparency is higher, voters are more likely to reward improvements in the quality of education.